Analisis Pengaruh Jumlah Penduduk, Investasi (PMDN), dan Belanja Langsung Terhadap Pertumbuhan Ekonomi Di Kabupaten/Kota Di Jawa Tengah Tahun 2015 – 2019 - Zukhrul Habib (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
The purpose of this study was to see how the independent variables, such as population, domestic investment, and direct expenditure, affect economic growth in Central Java's Regency/City. Panel data was used, which was collected from all districts in Central Java Province between 2015 and 2019. The method used is the multiple linear regression analysis method with the panel data regression method (pooled data), which will choose the best approach. Common, fixed, and random effects use a panel data regression test, namely the Chow Test, Hausman Test, and Lagrange Multiplier Test. The study results show that the population variable has a significant effect on economic growth. The domestic investment variable has a significant impact on economic growth, and the direct expenditure variable significantly impacts economic growth. Simultaneously, the variable Number of Population, Domestic Investment, and Direct Expenditure have a positive and significant impact on Economic Growth in Central Java.